2009
DOI: 10.1242/jcs.047738
|View full text |Cite
|
Sign up to set email alerts
|

A splice variant of cyclin D2 regulates cardiomyocyte cell cycle through a novel protein aggregation pathway

Abstract: D2SV to sequester other cell cycle proteins provides a mechanistic explanation for its effects on cardiomyocyte cell cycle. We show that D2SV-induced cell cycle exit can be rescued by overexpression of D-type and B-type cyclins. We suggest that protein aggregation may be a major block for cardiomyocyte cell cycle reactivation. Supplementary material available online at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 45 publications
(57 reference statements)
1
29
0
Order By: Relevance
“…Tissue lysates from pooled E11.5 or neonatal hearts were generated as previously described (40). Clear 96-well microtiter plates (Nunc, New York, NY; cat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue lysates from pooled E11.5 or neonatal hearts were generated as previously described (40). Clear 96-well microtiter plates (Nunc, New York, NY; cat.…”
Section: Methodsmentioning
confidence: 99%
“…A-21426) or goat anti-mouse Western blot analyses. Tissue lysates were prepared from pooled ventricles of different developmental stages, run on 12.5% polyacrylamide gels, and transferred to nitrocellulose membranes as previously described (40). For detecting the small 3-kDa ANP peptide, 16.5% gels were used and transfer was performed using Tris-tricine buffer (Bio-Rad) for shorter time periods.…”
Section: Methodsmentioning
confidence: 99%
“…It is known that the human and mouse truncated Cyclin D2 splice variant, D2SV, with a unique C terminus is also observed in cytoplasmic foci. 38 Our results indicate a possible cytoplasmic role of Cyclin Dbb/d variants during germline proliferation in O. dioica, with preferred localizations adjacent to syncytial nuclei during S-phase entry.…”
Section: Asynchronously Proliferating O Dioica Germ Nuclei Have a DImentioning
confidence: 57%
“…Under conditions of nutrient restriction, increased levels of mouse cytoplasmic D2SV splice variants 40 exert a suppressive role on cell cycle progression by sequestering key cell cycle regulators including cyclin D2, CDK4, Cyclin B and possibly p27. 36,38,39 Previously we have shown that the survival MAPK p38-MSK-1 signaling pathway is activated in the O. dioica mitotic germline during nutrient-dependent GA or when TOR signaling is inhibited. 8 Common responses to stress-induced p38 activation are cell cycle arrest or apoptosis.…”
Section: Altered Cyclin D Variant Expression In Response To Mapk P38 mentioning
confidence: 99%
See 1 more Smart Citation